Structural effect on the charge transfer and on the internal reorganization energy: Computational study - Jabha, Mohamed; El Alaoui, Abdelah; Jarid, Abdellah; Mabrouk, El Houssine (Eclética Química, 2022)
The effects of addition of thiophene, bridged phenyl-thiophene, thia-tetra-azacyclopenta-naphthalene, benzo-bis-thiadiazole, and pyrido(3,4-b)pyrazine to 9-(4-octyloxyphenyl)-2,7-divinylcabazole on the internal reorganization energies, electronic affinity, and ionization potential were studied using density functional theory (DFT). These compounds are characterized by their charge exchange potentials (donor-acceptor), which can be applied in energy conversion devices such as photovoltaic cells. The so-called internal reorganization concerns, above all, the positions of holes and points of high electron density on the molecular skeleton. Thus, valuable information is provided by the knowledge of the structure, the length of the desired oligomer and the nature of the radicals attached to the oligomer. Considering the available data, 2,7-divnyl-carbazole (CrV-H) is the basic oligomer to carry out this theoretical study by extending the choice of ligands and length order to other oligomers while setting charge mobility as the major objective. The λ+ of all the oligomers studied was lower than their λ– except for the CrV-BBT oligomer, indicating a lower hole transfer cost than electron transfer cost with changes in molecular geometry during this process.